2007
DOI: 10.1007/s11010-007-9458-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flavonoid on calcium content in femoral tissue culture and parathyroid hormone-stimulated osteoclastogenesis in bone marrow culture in vitro

Abstract: The effect of various flavonoids, which are present in food and plants, on bone calcium content and osteoclastogenesis were investigated to compare action of flavonoid on bone formation and bone resorption in vitro. Rat femoral-diaphyseal (cortical bone) and -metaphyseal (trabecular bone) tissues were cultured for 48 h in Dulbecco's modified Eagle's medium (high glucose) supplemented with antibiotics and bovine serum albumin. Amoung quercetin, myricetin, kaempferol, isorhamnetin, curcumin, hesperidin, or astax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…Recently, many researchers have reported that flavonoids showed good activity towards osteoporosis and inflammatory bone diseases. 13,14 In our work, the effects of isolated flavonoids compounds were carried out using a different cell line MC3T3-E1. Furthermore, the cell viability, ALP activity, collagen synthesis, and mineralization of MC3T3-E1 cell were studied systemically to check the effect of each sample.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many researchers have reported that flavonoids showed good activity towards osteoporosis and inflammatory bone diseases. 13,14 In our work, the effects of isolated flavonoids compounds were carried out using a different cell line MC3T3-E1. Furthermore, the cell viability, ALP activity, collagen synthesis, and mineralization of MC3T3-E1 cell were studied systemically to check the effect of each sample.…”
Section: Resultsmentioning
confidence: 99%
“…As recalled in the Introduction, flavonoids may interact with the biosynthesis of eumelanin, the most abundant pigment in blackbird feathers (McGraw, 2006). A key role in the link between flavonoids and moult may be played by a flavonoidmediated increase of calcium availability (Kanter et al, 2007;Yamaguchi et al, 2007). Melanin biosynthesis by melanocytes critically depends on limiting mineral elements, including calcium.…”
Section: Effects Of Dietary Flavonoids On Redox Status and Moultmentioning
confidence: 99%
“…Studies have reported that quercetin antagonizes bone resorption in femoral organ cultures (13) and in osteoclast differentiation and/or activation assays in vitro (14,15) by a mechanism that involves suppression of NF-κB and AP-1 (16). Interestingly, a quercetin-like varient, quercetin-6-C-β-D-glucopyranoside isolated from Ulmus wallichiana planchon has been demonstrated to possess enhanced anti-osteoclastogenic activity and to mitigate ovariectomy-induced bone loss in rats (17).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin has been reported to inhibit the proliferation, differentiation, and mineralization of osteoblasts in vitro (24) and promote TNFα-induced inhibition (25) and apoptosis (25,26). Other studies however, report increased alkaline phosphatase (an early osteoblast differentiation marker) levels in human MG-63 osteoblast cells (27) and stimulatory effects on bone formation in rat organ cultures ex vivo (13).…”
Section: Introductionmentioning
confidence: 99%